Equal and different : male and female in church and family - Harper, Michael (London, Hodder and Stoughton., 1994)
A new revised edition of this consideration of the gender debate after four years of the ordination of women in the Anglican church. The debate spans the biblical record, the lessons of history, the impact of feminism, and the nature of the family and calls for us to embrace our God-given differences and rejoice in the equality we share.
Keywords: Ordination of women.-- Christianity; Ordination of women.-- Church of England; Sex role.-- Religious aspects.-- Christianity